2021
DOI: 10.1093/jcag/gwab006
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Global Status and Its Impact in Crohn’s Disease

Abstract: Background Malnutrition among inflammatory bowel disease (IBD) subjects is well documented in literature and may emerge from factors including inadequate dietary intake, malabsorption and disease activity. The aim of this study was to complete a comprehensive nutrition assessment and explore what possibilities may help bring a better quality of life for IBD subjects. Methods Nutritional status based on biochemical tests, body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…[71][72][73][74] A study by Prieto JMI et al illustrated a similar relationship between low weight and micronutrient deficiency in CD patients who were underweight and deficient in micronutrients. 72 In summary, we found that VD was associated with both nutritional deficits and inflammation, and that nutritional deficit was associated with inflammation, suggesting that VD supplementation may play an anti-inflammatory role, improve nutritional status and thus improve prognosis. These findings provide new ideas for the clinical treatment of CD.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…[71][72][73][74] A study by Prieto JMI et al illustrated a similar relationship between low weight and micronutrient deficiency in CD patients who were underweight and deficient in micronutrients. 72 In summary, we found that VD was associated with both nutritional deficits and inflammation, and that nutritional deficit was associated with inflammation, suggesting that VD supplementation may play an anti-inflammatory role, improve nutritional status and thus improve prognosis. These findings provide new ideas for the clinical treatment of CD.…”
Section: Discussionmentioning
confidence: 84%
“…Treatment of monocytes with 1,25(OH)2D was found to inhibit lipopolysaccharide (LPS)‐induced p38 phosphorylation as well as IL‐6 and TNF‐ α production, thus preventing excessive activation of pro‐inflammatory responses 70 . Although VD is thought to be associated with nutritional status in CD patients, there have been few studies on the association between the serum VD level and nutritional status in CD patients 71–74 . A study by Prieto JMI et al illustrated a similar relationship between low weight and micronutrient deficiency in CD patients who were underweight and deficient in micronutrients 72 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nutritional status of patients with inflammatory bowel disease is often impaired, with malnutrition presenting as imbalanced energy or nutrient intake, including protein–energy malnutrition, disease-related malnutrition, sarcopenia, and micronutrient deficiency [ 37 ]. The pathogenesis of malnutrition involves several factors, such as reduced food intake, intestinal malabsorption, chronic loss of protein in stool, and increased energy requirements due to hypercatabolism [ 37 , 38 , 39 ]. In the present study, urinary excretion of sulfate and creatinine were significantly lower in patients with Crohn’s disease than in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…It involves malabsorption, corticosteroid treatment and the systemic inflammatory process itself, all of which may adversely affect the adequate formation of peak bone mass (up to the age of about 30 years), age-related loss of bone mass or both. Malnutrition might occur in patients with IBD from reduced dietary intake, malabsorption due to intestinal inflammation, short bowel syndrome after intestinal resection or increased energy requirements due to hypercatabolism [3]. In particu-lar, calcium and vitamin D deficiencies are detrimental to bone health and mineralisation, especially in combination with physical inactivity and decreased exposure to sunshine in patients with active disease.…”
Section: Pathophysiology Of Inflammatory Bowel Disease-associated Bon...mentioning
confidence: 99%